1992
DOI: 10.3354/meps087087
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced bacterioplankton production and respiration at intermediate salinities in the Mississippi River plume

Abstract: Bacterial abundance and production (thymidine and leucine incorporation) were measured along a salinity gradient from the Mississippi Rlver (0 %o) to the open waters of the Gulf of Mexico (36 %a) during July-August 1990 and February 1991. Bactenal production in surface waters was maximal at intermediate salinities (15 to 30 %o). Nutrlent enrichment experiments suggested that bacterial growth near the outflow of the river was C limited whereas bacteria in plume waters of intermediate salinities were P and N lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
66
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(77 citation statements)
references
References 39 publications
10
66
1
Order By: Relevance
“…In agreement with the present study, maximum bacterial abundance at low salinities near the river mouth was reported by Chin-Leo & Benner (1992). Maximum bacterial production sometimes occurs further downstream the salinity gradient than maximum abundance (Chin-Leo & Benner 1992, Pakulski et al 2000.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In agreement with the present study, maximum bacterial abundance at low salinities near the river mouth was reported by Chin-Leo & Benner (1992). Maximum bacterial production sometimes occurs further downstream the salinity gradient than maximum abundance (Chin-Leo & Benner 1992, Pakulski et al 2000.…”
Section: Discussionsupporting
confidence: 81%
“…Knowledge of bacterioplankton in the open Gulf of Mexico is scarce (Biddanda & Benner 1997) because most studies concentrated on the Mississippi River plume and Louisiana shelf waters (Chin-Leo & Benner 1992, Amon & Benner 1998, Pakulski et al 2000. Vertical and regional patterns in bacterioplankton diversity were addressed by quantification of morphologically distinguished bacteria using epifluorescence microscopy and of subpopulations with different apparent DNA content using flow cytometry.…”
Section: Introductionmentioning
confidence: 99%
“…al., 1995 . Other investigations, however, focus on photochemical and microbial transformations of terrigenous DOM, which may contribute to the produc-Ž tivity in these nearshore systems Moran et al, 1991;Chin-Leo and Benner, 1992;Bushaw et al, 1996; . Opsahl and Benner, 1997 .…”
Section: Introductionmentioning
confidence: 99%
“…Respiration due to bacterioplankton, at this time, was assumed to be 70% of the total plankton respiration. This assumption was based on previous measurements of bacterial respiration ranging from 40 to 100% of plankton respiration for different marine environments (Williams 1981, Chin-Leo & Benner 1992, Biddanda et al 1994). …”
Section: Introductionmentioning
confidence: 99%